STUDENTS' COLLABORATIVE SKILLS WITH AN APPROACH ETHNO-STEAM PROJECT OTK-OTOK GAME CONTEXT IN MATHEMATICS LEARNING - Nasution, Marah Doly; Nasution, Ismail Saleh; Sari, Suci Perwita (UIN Sumatera Utara Medan, 2024)
The traditional otok-otok game as a STEAM (Science, Technology, Engineering, Art, and Mathematics) based project can be used for mathematics learning. Research like this has never been done. The aim of this research is to describe students' collaborative skills through the Ethno-STEAM Project learning approach. The research subjects were 32 students with a pre-experimental research type with a one-shot case study design. Data regarding students' collaborative skills was obtained from student self-report questionnaires and data was strengthened through collaborative activity observation sheet forms. Data analysis uses descriptive statistics in the form of total scores and average percentages for each aspect or subdomain. The application of Ethno-STEAM Project learning in the context of otok-otok games produced results, namely that students' collaborative skills were in the high category 56%, in the medium category 31%, and in the low category 13%. Aspects of collaborative skills in the high category include motivation, contribution, problem-solving, time management, group dynamics, and interaction with group members. Aspects that need further development are in the categories of work quality, group support, readiness, roles, and reflection. The application of the Ethno-STEAM approach to the otok-otok game project in mathematics learning can be an alternative for developing students' collaborative skills